Mortality After Complex Displaced Proximal Humerus Fractures in Elderly Patients: Conservative Versus Operative Treatment With Reverse Total Shoulder Arthroplasty. (8th September 2018) - Rotman, Dani; Giladi, Ornit; Senderey, Adi Berliner; Dallich, Alison; Dolkart, Oleg; Kadar, Assaf; Maman, Eran; Chechik, Ofir
Introduction: Proximal humerus fractures (PHFs) are a common fragility fracture and have been shown to increase mortality in elderly patients. In the last decade, reverse total shoulder arthroplasty (RTSA) was introduced as a reliable operative treatment option for this indication. In other fragility fractures, most notably hip fractures, urgent surgical treatment can reduce mortality. The purpose of this study is to evaluate whether treatment with RTSA can reduce 1-year mortality in elderly patients with complex displaced PHFs. Materials and Methods: A retrospective study was performed to compare 1-year mortality between 2 groups of elderly patients (>75 years old) who presented to a level 1 trauma center emergency department with complex displaced PHFs. The conservative treatment group (n = 83; mean age, 83.7 years) presented from 2008 to 2010 when RTSA was not yet available, and treatment was nonoperative. The surgical treatment group (n = 62; mean age, 82.2 years) presented from 2012 to 2015 and underwent RTSA. Results: One-year mortality was 8.1% (male 7.1%; female 8.3%) in the surgical treatment group and 10.8% (male 18.8%; female 9.0%) in the conservative treatment group. The reduction in mortality in the surgical treatment group was not significant (entire cohort P = .56; males P = .35; females P = .59). Discussion: Recent studies failed to show better functional results after surgical treatment with RTSA when compared to conservative treatment. This study suggests that a benefit of surgical treatment with RTSA that was not examined until now might exist—a reduction in the increased mortality risk associated with PHFs. Conclusions: There was no significant difference in 1-year mortality between the groups, although there was a trend showing lower mortality with RTSA, mostly in men. Further studies with larger populations and longer follow-up times are needed to determine whether this trend is of clinical significance.